2007
DOI: 10.1080/15710880701327862
|View full text |Cite
|
Sign up to set email alerts
|

Exploring users' product constructs: how people think about different types of product

Abstract: A repertory grid-based study (n ¼ 20) investigated the issues that people identify when considering different types of products. Participants were each presented with four sets of three stimuli, each representing a different product type. For each set of stimuli they were asked to pick an 'odd-one-out' and to describe why they had placed it apart from the other two in the set. Participants' responses differed markedly by product type. This suggests that approaches to affective design need to be seen in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…human values [13]) will moderate the importance individuals attach to different qualities of an interactive product [7,1]; while some might prefer playful and stimulating products, others might value simplicity and austerity in products. Second, the type of the product will matter [6]; while a playful interaction might be crucial for the success of a computer game, the same quality might be perceived as inadequate for professional software. Third, even for the same product, the way we use it will differ across situations and this will impact the importance we attach to different qualities [4]; the same mobile phone could be used for exploring the available ring tones or to make an emergency call.…”
Section: Introductionmentioning
confidence: 99%
“…human values [13]) will moderate the importance individuals attach to different qualities of an interactive product [7,1]; while some might prefer playful and stimulating products, others might value simplicity and austerity in products. Second, the type of the product will matter [6]; while a playful interaction might be crucial for the success of a computer game, the same quality might be perceived as inadequate for professional software. Third, even for the same product, the way we use it will differ across situations and this will impact the importance we attach to different qualities [4]; the same mobile phone could be used for exploring the available ring tones or to make an emergency call.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, the questionnaires on Anticipated and Remembered UX allowed us to associate the evaluation on expectations and memories to specific functionality of the product. The importance of such judgement was recognised also by Jordan and Persson [17] who suggested a hierarchical structure of qualities that contribute to positive experience, having the functionality of the product as a baseline. In addition to Jordan and Persson [17], we assumed the importance of UX qualities to vary with several personal and contextual factors including time as a fundamental source of diversity in UX, considered in its many facets Anticipated, Momentary, Episodic and Remembered.…”
mentioning
confidence: 99%
“…Hence, an emotional requirements management system that is developed with a single modality (e.g., visual impression) may not be able to explain the UX of tactile-dominant products like sports equipment. Furthermore, research has shown that a user's mind construct model varies across product categories so as to affect his or her product evaluation (Jordan & Persson, 2007;Schifferstein, 2009).…”
Section: Research Gapmentioning
confidence: 99%